Microelectrode Array With Transparent ALD TiN Electrodes - Ryynänen, Tomi; Pelkonen, Anssi; Grigoras, Kestutis; Ylivaara, Oili M. E.; Hyvärinen, Tanja; Ahopelto, Jouni; Prunnila, Mika; Narkilahti, Susanna; Lekkala, Jukka (Frontiers in Neuroscience, 2019)
Low noise platinum black or sputtered titanium nitride (TiN) microelectrodes are typically used for recording electrical activity of neuronal or cardiac cell cultures. Opaque electrodes and tracks, however, hinder the visibility of the cells when imaged with inverted microscope, which is the standard method of imaging cells plated on microelectrode array (MEA). Even though transparent indium tin oxide (ITO) electrodes exist, they cannot compete in impedance and noise performance with above-mentioned opaque counterparts. In this work, we propose atomic layer deposition (ALD) as the method to deposit TiN electrodes and tracks which are thin enough (25-65 nm) to be transparent (transmission 18-45 %), but still benefit from the columnar structure of TiN, which is the key element to decrease noise and impedance of the electrodes. For ALD TiN electrodes (diameter 30 µm) impedances from 510 kΩ to 590 kΩ were measured at 1 kHz, which is less than the impedance of bare ITO electrodes. Human induced pluripotent stem cell (hiPSC)-derived cortical neurons were cultured on the ALD TiN MEAs for 14 days without observing any biocompatibility issues, and spontaneous electrical activity of the neurons was recorded successfully. The results show that transparent ALD TiN film is a suitable electrode material for producing functional MEAs.